Temperature stimulated bandgap tailoring in the smart chromogenic WO30.33H2O. Issue 1 (1st October 2022) - Manuja, M; Thomas, Tintu; Jose, Gijo
Abstract : The orthorhombic form of WO3 0.33H2 O is prepared hydrothermally and the thermochromic property of the material is identified using spectroradiometer with in a wavelength range of 325 nm to 1075 nm. The variation of reflectance with temperature is observed and it is accompanied with a change in bandgap. The absorbance relation with temperature is analyzed and the presence of Inter Valence Charge Transfer (IVCT) band is detected in the absorbance spectra. The IVCT bands illustrate the homovalent charge transfer mechanism behind the thermochromism taking place in the compound. The change in bandgap with temperature provides further supportive evidence to the thermochromic phenomenon observed in the compound.